Heissiella donguri sp. nov. (Hemiptera: Heteroptera: Tingidae) feeding on Quercus gilva (Fagaceae): First representative of the genus from Japan - Souma, Jun; Ishikawa, Tadashi (Zootaxa, 2020)
The lace bug genus Heissiella Péricart, 1984 (Hemiptera: Heteroptera: Tingidae) is recorded from Japan for the first time, and a new species, which has been recorded as ‘Tingis (Tropidocheila) sp.’ or ‘Tingis (Tropidocheila) shaowuana Drake & Maa, 1953’ (misidentification) by previous authors, is described under the name of H. donguri sp. nov. This new species was found on the leaves of Quercus gilva Blume (Fagaceae) in the laurilignosa ecosystem of Honshu and Kyushu, extending the known distribution range of the genus into the Palaearctic Region. The distribution range and the host plant relationship of the new species are discussed. A key to all described species of the genus and a photograph of a living individual for the new species are also presented.